2008
DOI: 10.3189/172756408787814924
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of seasonal snow-cover distribution for glacierized sites on Sonnblick, Austria, with the Alpine3D model

Abstract: A detailed model of Alpine surface processes is used to simulate the amount of preferential deposition as well as redistribution of snow due to snowdrift for two alpine glaciers (Goldbergkees and Kleinfleißkees, Austrian Alps). The sequence of snow-cover modelling consists of the simulation of the wind field with a mesoscale atmospheric model, a three-dimensional finite-element drift module, an energy-balance module and a snowpack module. All modules with the exception of the wind-field model are integrated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 17 publications
1
68
0
Order By: Relevance
“…Wind transport of snow is not considered in this model implementation. New-snow density and snow albedo parameterizations used in previous studies in the European Alps were found to work well in the Wolverton basin (Musselman et al, 2012a) and are used in the current study. Other land-cover parameters such as canopy height and leaf area index were specified according to land-cover classifications discussed in Sect.…”
Section: Snow Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Wind transport of snow is not considered in this model implementation. New-snow density and snow albedo parameterizations used in previous studies in the European Alps were found to work well in the Wolverton basin (Musselman et al, 2012a) and are used in the current study. Other land-cover parameters such as canopy height and leaf area index were specified according to land-cover classifications discussed in Sect.…”
Section: Snow Modelmentioning
confidence: 99%
“…It has been used in previous snow process studies (Bavay et al, 2009;Magnusson et al, 2011;Michlmayr et al, 2008;Mott et al, 2008) and projections of future snow or runoff (e.g., Bavay et al, 2009Bavay et al, , 2013Kobierska et al, 2011Kobierska et al, , 2013Marty et al, 2017). At the core of Alpine3D is the one-dimensional SNOW-PACK model (Bartelt and Lehning, 2002), which has been validated in alpine (e.g., Etchevers et al, 2004) and forested (e.g., Rutter et al, 2009) environments, including a previous study in the Wolverton basin using a subset of the forcing and verification data presented herein (Musselman et al, 2012a). At each model grid cell, mass and energy balance equations for vegetation, snow, and soil columns are solved with external forcing provided by the atmospheric variables described in Sect.…”
Section: Snow Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In winter, glaciers accumulate precipitation as snow, which in the case of a positive mass balance, is transformed to firn and ice over time. Strong winds may cause significant amounts of snow drifts across or even away from the glacier (Mott et al, 2008). The ablation (mass loss) of the glacier during summer is predominately from snow and ice melt which is closely related to the incoming shortwave radiation balance at the glacier surface.…”
Section: Introductionmentioning
confidence: 99%
“…The fully distributed Alpine3D model is typically applied for detailed studies of small scale surface processes in alpine catchments where snow plays an important role (Lehning et al, 2006;Mott et al, 2008;Groot Zwaaftink et al, 2013). In alpine terrain, considering the length scales less than a few 100 m is important as on these scales, wind drifts determine the snow accumulation and local topography heavily influences the energy balance via the slope aspect, angle and local shading.…”
Section: Introductionmentioning
confidence: 99%